2019
DOI: 10.18805/lr-4121
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping for heat stress tolerance in chickpea (Cicer arietinum L.)

Abstract: Rising evidence of heat stress (HS) is appearing as one of the major challenges to crop performance including chickpea affecting plant growth and yield significantly. Unprecedented advancements in chickpea genomic resources have resulted in remarkable progress for genetic dissection of various complex traits including biotic and abiotic stresses. However, these genomic resources have been limitedly utilized for developing HS tolerance in chickpea. Thus, the present study was aimed to capture genetic variabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…In this sense, the identification and introgression of QTLs associated with heat tolerance can accelerate the breeding process and facilitate combining different desired traits in one single genotype. The genetic architecture of heat stress tolerance has been extensively studied in chickpea [ 106 , 116 , 117 ]. For example, Paul et al [ 106 ] identified four major QTLs controlling pod and grain yield traits on LG5 and LG6 under heat stress, which explained above 50% of the phenotypic variation of those traits.…”
Section: Breeding Approaches In Chickpeamentioning
confidence: 99%
See 2 more Smart Citations
“…In this sense, the identification and introgression of QTLs associated with heat tolerance can accelerate the breeding process and facilitate combining different desired traits in one single genotype. The genetic architecture of heat stress tolerance has been extensively studied in chickpea [ 106 , 116 , 117 ]. For example, Paul et al [ 106 ] identified four major QTLs controlling pod and grain yield traits on LG5 and LG6 under heat stress, which explained above 50% of the phenotypic variation of those traits.…”
Section: Breeding Approaches In Chickpeamentioning
confidence: 99%
“…For example, Paul et al [ 106 ] identified four major QTLs controlling pod and grain yield traits on LG5 and LG6 under heat stress, which explained above 50% of the phenotypic variation of those traits. Moreover, Jha et al [ 117 ] reported a QTL associated with chlorophyll content on LG6 at ~100 cM, explaining 17.2% of the phenotypic variation under heat stress. A total of 37 major QTLs across the genome for 12 different traits related to heat tolerance were identified [ 117 ].…”
Section: Breeding Approaches In Chickpeamentioning
confidence: 99%
See 1 more Smart Citation
“…QTLs for number of filled pods, total number of seeds per plot, grain yield per plot and % pod setting were reported using RIL population developed from ICC 4567 (heat sensitive) × ICC 15614 (heat tolerant) (Paul et al, 2018b). Using SSR markers, QTLs for primary branch number and chlorophyll content were reported in F 2 population derived from DCP 92-3 × ICCV 92944 (Jha et al, 2019). Additionally, Kushwah et al (2021b) reported QTLs for heat tolerance using an inter-specific RIL population derived from the cross GPF 2 (heat tolerant) × ILWC 292 (heat sensitive).…”
Section: Introductionmentioning
confidence: 99%
“…Low polymorphism limits the use of SSR markers in chickpea genotyping (Amina et al, 2020;Nayak et al, 2010;Gaur et al, 2012;Gujaria et al, 2011;Choudhary et al, 2012;Suman et al, 2018) due to which scientific community resorted to single nucleotide polymorphism (SNP) as an alternative to SSRs (Gaur et al, 2020). Since, SSR marker technology is within the reach of ordinary laboratories, it is highly desirable to develop new SSR markers for chickpea, so that genetic mapping of genes including quantitative trait loci (Jha et al, 2021) and marker assisted selection (Henkrar and Udupa, 2020) can become a routine procedure as is the case in crops like rice (Courtois et al, 2000).…”
Section: Introductionmentioning
confidence: 99%